ALA LAMPUNG RASA PALEMBANG: STRATEGI PEMASARAN “PEMPEK TARISA” HALAL - Haque, Marissa Grace (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Pempek is very synonymous with Palembang, it is said that it was first sold by Chinese traders in 1916 in Palembang. However, with the large diaspora of Palembang people nationally and internationally, Lampung is now also producing Pempek with flavors that are very competitive with the original producing city in Palembang. The research uses a mixed-method, with descriptive analysis to determine the existence of the company's survival ability "Pempek Tarisa Lampung." A special business strategy is needed in this halal-certified industry. Using the SWOT analysis measuring tool, internal-external weighting, the Four Step Strategy, determines the most appropriate strategy, in order to be able to overcome challenges by taking advantage of all possible opportunities. The results show several weaknesses that must be immediately corrected in order to optimize revenue potential, in the form of more extensive digital marketing, innovation in product variants, including embracing more public figures as catalysts to leverage. "PTL" will be more powerful in expanding marketing reach and increasing engagement with its customers. Apart from that, innovation in product variants is also needed to maintain the attractiveness and relevance of the business, so that it is able to continue to attract old customers, as well as attract the interest of new consumers. The cost leadership strategy, which had been successful previously, was maintained. In particular, by combining digital marketing strategies, product innovation, embracing more public figures, and cost leadership strategies, halal SMEs "PTL" can continue to develop and succeed in the halal SME culinary market which is now increasingly competitive. MSMEs (halal) are indeed an industry that saves the nation's economy, 10.79 million people (7.71 percent) of the Indonesian population work in providing accommodation and food and drink (BPS, 2023). So knowing the survival ability of industry players on a micro scale is very important to think about for sustainability.